Transaksi Trapeutik Sebagai Pertanggungjawaban Dokter Terhadap Pasien - Muhammad Darwis; Rahmat Amir (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This research was conducted to know the legal relationship between doctors and patients in accordance with the laws and regulations at the Barru Regional General Hospital and to find out the Legal Responsibilities of Doctors in Therapeutic Transactions with Patients at the Barru Regional General Hospital. The type of research used is normative or dogmatic research, using juridical and empirical approaches through interview formats. The results of the analysis of the data and facts found in the field, the authors are of the view that, the legal relationship between doctors and patients at the Barru Regional General Hospital, that what is stated in the therapeutic agreement is only an agreement between the doctor and the patient in the abstract. The primary responsibility of health workers (doctors, hospitals and other health workers) is an unlawful act (onrechtmatige daad). A doctor has acted against the law because his actions contradict the principles of decency, thoroughness and caution expected of him in dealing with fellow citizens. The author's recommendations for doctors at the Barru Regional General Hospital should have responsibility for explaining and providing understanding to patients or to the patient's family regarding the medical actions that will be carried out for the patient's recovery and for the community or the patient and the patient's family it is hoped that they will try to find out what becomes their rights as citizens with Treupatic Transactions carried out at hospitals or doctors before handling patients at the hospital.